Positive electrode material and preparation method thereof, lithium ion battery and electric equipment
By adding crystal growth guidance additives and semiconductor two-dimensional carrier additives to the method of preparing nickel-rich cathode materials, the problems of lithium-nickel mixing and the reaction of highly active materials and electrolytes are solved, and the high discharge capacity of the battery is achieved. , cycle retention rate and safety performance improvement.
Patent Information
- Application Number
- CN202411919084.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-12-25
AI Technical Summary
Nickel-rich positive electrode materials are prone to lithium-nickel mixed discharge during the sintering process and high-pressure deliquency state, which affects the charging and discharging efficiency and cycle stability of the battery; at the same time, high-active materials are prone to react with the electrolyte, resulting in transition metal dissolution and gas production. Reduce battery performance and bring safety risks.
A preparation method is adopted, in which the nickel-rich cathode material precursor is mixed with a lithium source and a crystal growth guide additive, and then pulverized, washed, and dried after the first sintering, and then mixed with a semiconductor two-dimensional carrier additive (such as metal tellurium compounds) are mixed for the second sintering to form the cathode material.
Through this method, the battery discharge capacity and circulation maintenance rate is effectively improved, the battery life and safety performance of the battery are improved, and the voltage attenuation and interface impedance are reduced.
Smart Images

Figure CN119349659A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium-ion batteries, and in particular to a positive electrode material and a preparation method thereof, a lithium-ion battery and an electrical device. Background Art
[0002] The vigorous development of new energy vehicles has put forward higher requirements on the performance of lithium-ion batteries, especially the pursuit of higher energy density and lower cost, in order to meet consumers' expectations for driving range and reduce the cost of use.
[0003] Nickel-rich cathode material (LiNi x Co y Mn 1-x-y O2, x≥ 0.8, y≥0), has attracted more and more attention due to its excellent discharge capacity and low cost advantages. With the further increase of Ni content, the discharge capacity and cost advantages of this type of material have become more and more significant, providing an important way to improve the energy density of the battery. However, the increase of Ni content also brings a series of technical challenges. First, during the sintering process of nickel-rich positive electrode materials and under high-voltage lithium delithiation, lithium-nickel mixing occurs frequently, resulting in obstruction of lithium ion diffusion channels, which seriously affects the charge and discharge efficiency and cycle stability of the battery. Second, highly active nickel-rich positive electrode materials are prone to adverse reactions with electrolytes, causing the dissolution of transition metals and gas generation, which not only reduces battery performance, but also brings potential safety hazards. Third, under high cut-off voltage conditions, nickel-rich positive electrode materials are prone to lattice oxygen escape and irreversible phase change, resulting in uneven stress distribution at the grain boundaries, and the particles are easy to pulverize, which seriously affects the structural integrity and long-term service life of the battery. Fourth, the thermal decomposition temperature of nickel-rich positive electrode materials is low, and the heat release is large, which significantly increases the safety risk of batteries in the case of thermal runaway, becoming one of the key factors restricting its commercial application.
[0004] How to effectively improve the safety performance of batteries while enhancing the electrochemical performance of new energy vehicle power batteries and alleviating consumers' mileage anxiety has become a core technical problem that needs to be urgently solved in the current new energy field. Summary of the invention
[0005] The purpose of the present application is to provide a positive electrode material and a preparation method thereof, a lithium ion battery and an electrical device to solve the above problems.
[0006] To achieve the above objectives, this application adopts the following technical solutions: A method for preparing a positive electrode material, comprising: Mixing a nickel-rich cathode material precursor with a lithium source and a crystal growth directing agent to obtain a raw material; The raw material is first sintered, crushed, washed and dried to obtain the material to be coated; The material to be coated is mixed with a semiconductor two-dimensional carrier auxiliary agent, and a second sintering is performed to obtain a positive electrode material; wherein the semiconductor two-dimensional carrier auxiliary agent includes metal telluride. According to an embodiment of the present application, the chemical formula of the positive electrode material precursor is Ni x Co y Mn 1-x-y (OH)2, where 0.80≤x≤0.96, 0≤y≤0.10; And / or, the lithium source comprises a lithium-containing compound or a hydrate of a lithium-containing compound, and the lithium-containing compound comprises at least one of LiOH, Li2CO3, CH3COOLi, and Li2C2O4; And / or, the molar ratio of the positive electrode material precursor to the lithium source is 1:(1.02-1.06); And / or, the cationic element of the crystal growth directing aid includes at least one of Na, Al, Mg, Si, W, Zr, Sr, and Ti, and the anionic element of the crystal growth directing aid includes at least one of O, S, P, and F.
[0007] According to an embodiment of the present application, the crystal growth guiding aid includes at least one of Na3AlF6, MgSiF6, and MgAl2Si2O8; And / or, based on the mass of the positive electrode material precursor, the total mass of the cationic elements in the crystal growth directing aid is 1000-3000 ppm.
[0008] According to an embodiment of the present application, the first sintering includes: heating from room temperature to a first temperature at a heating rate of 2-10°C / min, keeping the temperature at the first temperature for 2-7 hours, heating to a second temperature at a heating rate of 5-10°C / min after the temperature is kept, keeping the temperature at the second temperature for 10-14 hours, and cooling to room temperature at a rate of 1-3°C / min after the temperature is kept constant, the first temperature is 400-650°C, and the second temperature is 700-800°C; And / or, the first sintering is performed in a pure oxygen atmosphere or a mixed atmosphere with an oxygen concentration of ≥90%.
[0009] According to an embodiment of the present application, the metal in the metal telluride includes at least one of W, Mo, Sn, Sb, and Bi.
[0010] According to an embodiment of the present application, the metal telluride includes at least one of WTe2, MoTe2, SnTe, and Bi2Te3; And / or, based on the mass of the material to be coated, the content of the metal element in the metal telluride is 1000-2000 ppm.
[0011] According to an embodiment of the present application, the second sintering includes heating from room temperature to a third temperature at a heating rate of 2-8°C / min, keeping the temperature at the third temperature for 8-12 hours, and cooling to room temperature at a rate of 5-10°C / min after the insulation. The third temperature is 300-660°C.
[0012] The present application also provides a positive electrode material, which is prepared by the preparation method described above.
[0013] The present application also provides a lithium-ion battery, which includes the positive electrode material described above.
[0014] The present application also provides an electrical device, which includes the lithium-ion battery described above.
[0015] Compared with the prior art, the beneficial effects of this application include: The present application adds a crystal growth guiding agent and a semiconductor two-carrier auxiliary agent to the method for preparing a positive electrode material. The two support and cooperate with each other in function, which can effectively improve the discharge capacity and cycle retention rate of the battery, is conducive to improving the battery's cruising range and improving the battery's safety performance, and is of great significance for promoting the sustainable development of the new energy vehicle industry. Specifically, the positive electrode material uses a crystal growth guiding agent and a semiconductor two-dimensional carrier auxiliary agent to cooperate. The crystal growth guiding agent can induce the growth of the positive electrode material lattice, maintain the band gap width, hinder the migration of transition elements, improve the cycle stability, and reduce the voltage decay. The cationic elements in the crystal growth guiding agent can stabilize the basic crystal structure, increase the mechanical strength of the particles, expand the lithium ion transmission channel, reduce the internal stress caused by the change of the lattice volume, and improve the dynamics and thermal stability; at the same time, the semiconductor two-dimensional carrier auxiliary agent coating is conducive to the embedding and extraction of lithium ions, improves the charging and discharging efficiency and power performance, reduces the interface impedance, and avoids the positive electrode material from being directly eroded and collapsed by the electrolyte, thereby improving the electrode structure stability and battery cruising range. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0017] Figure 1 This is a SEM image of the positive electrode material of Example 1; Figure 2 This is a SEM image of the positive electrode material of Example 2; Figure 3 This is a SEM image of the positive electrode material of Example 3; Figure 4This is a SEM image of the positive electrode material of Example 4; Figure 5 This is a SEM image of the positive electrode material of Example 5; Figure 6 This is a SEM image of the positive electrode material of Example 6; Figure 7 This is a SEM image of the positive electrode material of Example 7; Figure 8 This is a SEM image of the positive electrode material of Example 8; Fig. 9 This is the SEM image of the positive electrode material of Comparative Example 1; Fig.10 This is the SEM image of the positive electrode material of Comparative Example 2; Fig.11 This is the SEM image of the positive electrode material of Comparative Example 3; Fig.12 This is the SEM image of the positive electrode material of Comparative Example 4; Fig.13 This is the SEM image of the positive electrode material of Comparative Example 5; Fig.14 This is the SEM image of the positive electrode material of Comparative Example 6; Fig.15 The XRD diffraction patterns of the positive electrode materials of Example 1 and Comparative Example 1 are shown. DETAILED DESCRIPTION
[0018] As used herein: "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0019] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0020] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0021] In these examples, parts and percentages are by mass unless otherwise indicated.
[0022] "Mass parts" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass parts of component A are a parts and the mass parts of component B are b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass parts of all components is not limited to 100 parts.
[0023] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0024] In order to better explain the technical solution provided by this application, before the embodiments, the technical solution is first described as a whole, as follows: A method for preparing a positive electrode material, comprising: Mixing a nickel-rich cathode material precursor with a lithium source and a crystal growth directing agent to obtain a raw material; The raw material is first sintered to obtain a material to be coated; The material to be coated is mixed with a semiconductor two-dimensional carrier auxiliary agent, and a second sintering is performed to obtain a positive electrode material; wherein the semiconductor two-dimensional carrier auxiliary agent includes a metal telluride. According to the embodiment of the present application, the chemical formula of the positive electrode material precursor is Ni x Co y Mn 1-x-y (OH)2, where 0.80≤x≤0.96, 0≤y≤0.10; The chemical formula of the cathode material precursor includes but is not limited to Ni 0.8 Mn 0.2 (OH)2、Ni 0.8 Co0.1 Mn 0.1 (OH)2、Ni 0.96 Mn 0.04 (OH)2、Ni 0.92 Co 0.05 Mn 0.03 (OH)2.
[0025] And / or, the lithium source includes a lithium-containing compound or a hydrate of a lithium-containing compound, the lithium-containing compound includes at least one of LiOH, Li2CO3, CH3COOLi, and Li2C2O4; the hydrate of the lithium-containing compound refers to a lithium-containing compound containing crystalline water, and illustratively, the hydrate of the lithium-containing compound includes but is not limited to LiOH·H2O.
[0026] The lithium source is preferably a micron-sized lithium source, for example, the D50 of the lithium source satisfies 10 μm≤D50≤16 μm.
[0027] And / or, the molar ratio of the positive electrode material precursor to the lithium source is 1:(1.02~1.06); for example, the molar ratio of the positive electrode material precursor to the lithium source can be 1:1.02, 1:1.03, 1:1.04, 1:1.05, 1:1.06 or any value between 1:(1.02~1.06).
[0028] And / or, the cationic element of the crystal growth directing aid includes at least one of Na, Al, Mg, Si, W, Zr, Sr, and Ti, and the anionic element of the crystal growth directing aid includes at least one of O, S, P, and F.
[0029] According to an embodiment of the present application, the crystal growth guiding aid includes at least one of Na3AlF6, MgSiF6, and MgAl2Si2O8; By adding a crystal growth guiding agent to the method for preparing a positive electrode material, the lattice growth of the positive electrode material can be induced. First, the crystal growth guiding agent of the present application contains a variety of cationic elements, which can effectively stabilize the basic crystal structure, increase the mechanical strength of the particles, expand the lithium ion transmission channel, and improve the kinetics and rate performance; second, the crystal growth guiding agent can induce lattice growth, maintain the band gap width, hinder the migration of nickel, cobalt, and manganese transition elements, improve cycle stability, and reduce voltage attenuation; third, non-metallic elements (F, Si and other elements) are doped to occupy oxygen vacancies, increase the interlayer and intralayer chemical bond energy, reduce the lattice volume change during the cycle, and induce shortening of the diffusion path of lithium ions in the lattice structure, reduce the internal stress caused by the lattice volume change, improve the overall cycle performance and thermal stability of the material, and improve safety.
[0030] According to some embodiments of the present application, the crystal growth directing aid includes secondary particles formed by aggregation of multiple primary particles, the size of the crystal growth directing aid is micrometer-scale, the size of the primary particles is nanometer-scale, and the size of the primary particles is preferably less than 100 nm.
[0031] And / or, based on the mass of the positive electrode material precursor, the total mass of the cationic elements in the crystal growth directing aid is 1000~3000ppm.
[0032] For example, based on the mass of the positive electrode material precursor, the total mass of the cationic elements in the crystal growth directing aid can be 1000 ppm, 1500 ppm, 2000 ppm, 2500 ppm, 3000 ppm or any value between 1000 and 3000 ppm.
[0033] According to an embodiment of the present application, the first sintering includes: heating from room temperature at a heating rate of 2 to 10°C / min (for example, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min or any value between 2 and 10°C / min) to a first temperature, keeping the temperature at the first temperature for 2 to 7 hours (for example, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours or any value between 2 and 7 hours), and heating at a heating rate of 5 to 10°C / min (for example, 5°C / min, 6°C / min, , 7°C / min, 8°C / min, 9°C / min, 10°C / min or any value between 5 and 10°C / min) to a second temperature, maintaining the temperature at the second temperature for 10 to 14 hours (for example, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours or any value between 10 and 14 hours), and cooling to room temperature at a rate of 1 to 3°C / min (for example, 1°C / min, 2°C / min, 3°C / min or any value between 1 to 3°C / min), the first temperature is 400 to 650°C, and the second temperature is 700 to 800°C; For example, the first temperature may be 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, or any value between 400 and 650°C.
[0034] The second temperature may be 700° C., 750° C., 800° C., or any value between 700° C. and 800° C. The second temperature is preferably 757° C. to 767° C.
[0035] And / or, the first sintering is performed in a pure oxygen atmosphere or a mixed atmosphere with an oxygen concentration of ≥ 90%. For example, the gas introduction rate may be 20-60 L / h.
[0036] According to some embodiments of the present application, after the first sintering is completed, the method further includes: cooling the product after the first sintering, and then crushing, washing, centrifuging, and drying to obtain the material to be coated.
[0037] According to an embodiment of the present application, the metal in the metal telluride includes at least one of W, Mo, Sn, Sb, and Bi.
[0038] According to an embodiment of the present application, the metal telluride includes at least one of WTe2, MoTe2, SnTe, and Bi2Te3.
[0039] By adding metal telluride as a semiconductor two-dimensional carrier additive in the method of preparing positive electrode materials, it is beneficial to improve the electrochemical performance of positive electrode materials. First, metal telluride has a large specific surface area, and its uniform coating on the surface of positive electrode materials is conducive to full contact between electrode materials and electrolytes, which is conducive to the insertion and extraction of lithium ions, and improves the battery charging and discharging efficiency and power performance; second, the covalent bonds in the metal telluride layer give it high mechanical strength. After the metal telluride is coated on the surface of the material, the electrode material can be prevented from being directly corroded and collapsed by the electrolyte, which is beneficial to improve the interface stability of the positive electrode material during the cycle process and improve the cycle life; third, metal telluride has a high carrier mobility, which is conducive to improving the transmission rate of lithium ions, effectively reducing the interface impedance of the positive electrode material and improving the kinetic performance of the material.
[0040] According to some embodiments of the present application, the size of the metal telluride is nanoscale, and the size of the metal telluride is preferably less than 500 nm.
[0041] And / or, based on the mass of the material to be coated, the content of the metal element in the metal telluride is 1000-2000 ppm.
[0042] For example, based on the mass of the material to be coated, the content of metal elements in the metal telluride can be 1000ppm, 1100ppm, 1200ppm, 1300ppm, 1400ppm, 1500ppm, 1600ppm, 1700ppm, 1800ppm, 1900ppm, 2000ppm or any value between 1000-2000ppm.
[0043] According to an embodiment of the present application, the second sintering includes heating from room temperature at a heating rate of 2~8℃ / min (for example, 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min or any value between 2~8℃ / min) to a third temperature, keeping the temperature at the third temperature for 8~12h (for example, 8h, 9h, 10h, 11h, 12h or any value between 8~12h), and cooling to room temperature at a rate of 5~10℃ / min (for example, 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, 10℃ / min or any value between 5~10℃ / min) after the insulation, and the third temperature is 300~660℃.
[0044] For example, the third temperature may be 300° C., 350° C., 400° C., 450° C., 500° C., 550° C., 600° C., 660° C., or any value between 300° C. and 660° C. The third temperature is preferably 615° C. to 625° C.
[0045] The present application also provides a positive electrode material, which is prepared by the above-mentioned preparation method.
[0046] The present application also provides a lithium-ion battery, which includes the positive electrode material described above.
[0047] The present application also provides an electrical device, which includes the lithium-ion battery described above.
[0048] The electrical equipment includes but is not limited to electric bicycles, electric vehicles, drones, power tools, smart phones, tablet computers, laptops, e-book readers, portable game consoles, digital cameras and camcorders, Bluetooth headsets, and smart watches.
[0049] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0050] 1. Preparation of positive electrode materials Example 1 Embodiment 1 provides a positive electrode material, and the preparation method thereof comprises: (1) Weigh 5 kg of nickel-rich precursor Ni at a molar ratio of 1:1.03 0.92 Co 0.05 Mn 0.03(OH)2 and 2.33kgLiOH·H2O, and 21.9g (2000ppm) Na3AlF6 are added at the same time, and mixed at a high speed in a high-speed mixer. After mixing, the mixture is put into a bowl and placed in a box furnace in a pure oxygen atmosphere (inlet rate 40L / h), and the temperature is first increased to a first temperature of 520℃ at a rate of 5℃ / min and kept constant for 4h. After the constant temperature is reached, the temperature is increased to a second temperature of 762℃ at a rate of 7℃ / min and kept constant for 12.5h. After the constant temperature is reached, the temperature is lowered to room temperature at a rate of 2℃ / min, and the material B to be coated is obtained by crushing, washing, centrifuging, and drying; (2) Take 5 kg of the material B to be coated and 18 g (1500 ppm) of WTe2 and add them into a high-speed mixer for high-speed mixing and dispersion. After the mixing is completed, put them into a box furnace and heat them to the third temperature of 620°C at a rate of 3°C / min in a pure oxygen atmosphere (inlet rate of 25 L / h), and keep the temperature constant for 11 hours. After the constant temperature is completed, cool it to room temperature at a rate of 5°C / min. After the cooling is completed, the positive electrode material is obtained.
[0051] Example 2 Embodiment 2 provides a positive electrode material, and the preparation method thereof comprises: (1) Weigh 5 kg of nickel-rich precursor Ni at a molar ratio of 1:1.03 0.92 Co 0.05 Mn 0.03 (OH)2 and 2.33kgLiOH·H2O, and 31.9g (2000ppm) MgSiF6 are added at the same time, and mixed at a high speed in a high-speed mixer. After mixing, the mixture is put into a bowl and placed in a box furnace in a pure oxygen atmosphere (inlet rate 40L / h), and the temperature is first increased to a first temperature of 520℃ at a rate of 5℃ / min and kept constant for 4h. After the constant temperature is reached, the temperature is increased to a second temperature of 762℃ at a rate of 7℃ / min, and kept constant for 12.5h. After the constant temperature is reached, the temperature is lowered to room temperature at a rate of 2℃ / min, and the material B to be coated is obtained by crushing, washing, centrifuging, and drying; (2) Take 5 kg of the material B to be coated and 18 g (1500 ppm) of WTe2 and add them into a high-speed mixer for high-speed mixing and dispersion. After the mixing is completed, put them into a box furnace and heat them to the third temperature of 620°C at a rate of 3°C / min in a pure oxygen atmosphere (inlet rate of 25 L / h), and keep the temperature constant for 11 hours. After the constant temperature is completed, cool it to room temperature at a rate of 5°C / min. After the cooling is completed, the positive electrode material is obtained.
[0052] Example 3 Embodiment 3 provides a positive electrode material, and the preparation method thereof comprises: (1) Weigh 5 kg of nickel-rich precursor Ni at a molar ratio of 1:1.03 0.92 Co 0.05 Mn 0.03(OH)2 and 2.33kgLiOH·H2O, and 19.6g (2000ppm) MgAl2Si2O8 are added at the same time, and mixed at a high speed in a high-speed mixer. After mixing, the mixture is put into a bowl and placed in a box furnace in a pure oxygen atmosphere (inlet rate 40L / h), and the temperature is first increased to a first temperature of 520℃ at a rate of 5℃ / min and kept constant for 4h. After the constant temperature is reached, the temperature is increased to a second temperature of 762℃ at a rate of 7℃ / min and kept constant for 12.5h. After the constant temperature is reached, the temperature is lowered to room temperature at a rate of 2℃ / min, and the material B to be coated is obtained by crushing, washing, centrifuging and drying; (2) Take 5 kg of the material B to be coated and 18 g (1500 ppm) of WTe2 and add them into a high-speed mixer for high-speed mixing and dispersion. After the mixing is completed, put them into a box furnace and heat them to the third temperature of 620°C at a rate of 3°C / min in a pure oxygen atmosphere (inlet rate of 25 L / h), and keep the temperature constant for 11 hours. After the constant temperature is completed, cool it to room temperature at a rate of 5°C / min. After the cooling is completed, the positive electrode material is obtained.
[0053] Example 4 Embodiment 4 provides a positive electrode material, and the preparation method thereof comprises: (1) Weigh 5 kg of nickel-rich precursor Ni at a molar ratio of 1:1.03 0.92 Co 0.05 Mn 0.03 (OH)2 and 2.33kgLiOH·H2O, and 21.9g (2000ppm) Na3AlF6 are added at the same time, and mixed at a high speed in a high-speed mixer. After mixing, the mixture is put into a bowl and placed in a box furnace in a pure oxygen atmosphere (inlet rate 40L / h), and the temperature is first increased to a first temperature of 520℃ at a rate of 5℃ / min and kept constant for 4h. After the constant temperature is reached, the temperature is increased to a second temperature of 762℃ at a rate of 7℃ / min and kept constant for 12.5h. After the constant temperature is reached, the temperature is lowered to room temperature at a rate of 2℃ / min, and the material B to be coated is obtained by crushing, washing, centrifuging, and drying; (2) Take 5 kg of the material B to be coated and 27.45 g (1500 ppm) of MoTe2 and add them into a high-speed mixer for high-speed mixing and dispersion. After the mixing is completed, put them into a box furnace and heat them to a third temperature of 620°C at a rate of 3°C / min in a pure oxygen atmosphere (inlet rate of 25 L / h). Keep the temperature constant for 11 hours, cool it to room temperature at a rate of 5°C / min, and obtain the positive electrode material after the cooling is completed.
[0054] Example 5 Embodiment 5 provides a positive electrode material, and the preparation method thereof comprises: (1) Weigh 5 kg of nickel-rich precursor Ni at a molar ratio of 1:1.03 0.92 Co 0.05 Mn0.03 (OH)2 and 2.33kgLiOH·H2O, and 21.9g (2000ppm) Na3AlF6 are added at the same time, and mixed at a high speed in a high-speed mixer. After mixing, the mixture is put into a bowl and placed in a box furnace in a pure oxygen atmosphere (inlet rate 40L / h), and the temperature is first increased to a first temperature of 520℃ at a rate of 5℃ / min and kept constant for 4h. After the constant temperature is reached, the temperature is increased to a second temperature of 762℃ at a rate of 7℃ / min and kept constant for 12.5h. After the constant temperature is reached, the temperature is lowered to room temperature at a rate of 2℃ / min, and the material B to be coated is obtained by crushing, washing, centrifuging, and drying; (2) Take 5 kg of the material B to be coated and 15.6 g (1500 ppm) of SnTe and add them into a high-speed mixer for high-speed mixing and dispersion. After the mixing is completed, put them into a box furnace and heat them to a third temperature of 620°C at a rate of 3°C / min in a pure oxygen atmosphere (inlet rate of 25 L / h). Keep the temperature constant for 11 hours. After the constant temperature is completed, cool it to room temperature at a rate of 5°C / min. After the cooling is completed, the positive electrode material is obtained.
[0055] Example 6 Embodiment 6 provides a positive electrode material, and the preparation method thereof comprises: (1) Weigh 5 kg of nickel-rich precursor Ni at a molar ratio of 1:1.03 0.92 Co 0.05 Mn 0.03 (OH)2 and 2.33kgLiOH·H2O, and 21.9g (2000ppm) Na3AlF6 are added at the same time, and mixed at a high speed in a high-speed mixer. After mixing, the mixture is put into a bowl and placed in a box furnace in a pure oxygen atmosphere (inlet rate 40L / h), and the temperature is first increased to a first temperature of 520℃ at a rate of 5℃ / min and kept constant for 4h. After the constant temperature is reached, the temperature is increased to a second temperature of 762℃ at a rate of 7℃ / min and kept constant for 12.5h. After the constant temperature is reached, the temperature is lowered to room temperature at a rate of 2℃ / min, and the material B to be coated is obtained by crushing, washing, centrifuging, and drying; (2) Take 5 kg of the material B to be coated and 14.4 g (1500 ppm) of Bi2Te3 and add them into a high-speed mixer for high-speed mixing and dispersion. After the mixing is completed, put them into a box furnace and heat them to a third temperature of 620°C at a rate of 3°C / min in a pure oxygen atmosphere (inlet rate of 25 L / h). Keep the temperature constant for 11 hours, cool them to room temperature at a rate of 5°C / min, and obtain the positive electrode material after the cooling is completed.
[0056] Example 7 The positive electrode material was prepared by referring to the method of Example 1. The other steps were the same as those of Example 1, except that the second temperature in step (1) of Example 7 was 772°C.
[0057] Example 8 The positive electrode material was prepared by referring to the method of Example 1. The other steps were the same as those of Example 1, except that the third temperature in step (2) of Example 8 was 610°C.
[0058] Comparative Example 1 (1) Weigh 5 kg of nickel-rich precursor Ni at a molar ratio of 1:1.03 0.92 Co 0.05 Mn 0.03 (OH)2 and 2.33kgLiOH·H2O are mixed at high speed in a high-speed mixer. After mixing, the mixture is put into a bowl and placed in a box furnace in a pure oxygen atmosphere (inlet rate of 40L / h). The temperature is first raised to a first temperature of 520°C at a rate of 5°C / min and kept constant for 4h. After the constant temperature is reached, the temperature is raised to a second temperature of 762°C at a rate of 7°C / min and kept constant for 12.5h. After the constant temperature is reached, the temperature is lowered to room temperature at a rate of 2°C / min, and the material B to be coated is obtained by crushing, washing, centrifuging and drying. (2) Take 5 kg of the material B to be coated and 18 g (1500 ppm) of WTe2 and add them into a high-speed mixer for high-speed mixing and dispersion. After the mixing is completed, put them into a box furnace and heat them to the third temperature of 620°C at a rate of 3°C / min in a pure oxygen atmosphere (inlet rate of 25 L / h), and keep the temperature constant for 11 hours. After the constant temperature is completed, cool it to room temperature at a rate of 5°C / min. After the cooling is completed, the positive electrode material is obtained.
[0059] Comparative Example 2 (1) Weigh 5 kg of nickel-rich precursor Ni at a molar ratio of 1:1.03 0.92 Co 0.05 Mn 0.03 (OH)2 and 2.33kgLiOH·H2O, and 5.5g (500ppm) Na3AlF6 are added at the same time, and mixed at a high speed in a high-speed mixer. After mixing, the mixture is put into a bowl and placed in a box furnace in a pure oxygen atmosphere (inlet rate 40L / h), and the temperature is first increased to a first temperature of 520℃ at a rate of 5℃ / min and kept constant for 4h. After the constant temperature is completed, the temperature is increased to a second temperature of 762℃ at a rate of 7℃ / min, and kept constant for 12.5h. After the constant temperature is completed, the temperature is cooled to room temperature at a rate of 2℃ / min, and the material B to be coated is obtained by crushing, washing, centrifuging, and drying; (2) Take 5 kg of the material B to be coated and 18 g (1500 ppm) of WTe2 and add them into a high-speed mixer for high-speed mixing and dispersion. After the mixing is completed, put them into a box furnace and heat them to the third temperature of 620°C at a rate of 3°C / min in a pure oxygen atmosphere (inlet rate of 25 L / h), and keep the temperature constant for 11 hours. After the constant temperature is completed, cool it to room temperature at a rate of 5°C / min. After the cooling is completed, the positive electrode material is obtained.
[0060] Comparative Example 3 (1) Weigh 5 kg of nickel-rich precursor Ni at a molar ratio of 1:1.03 0.92 Co 0.05 Mn 0.03 (OH)2 and 2.33kgLiOH·H2O, and 38.3g (3500ppm) Na3AlF6 are added at the same time, and mixed at a high speed in a high-speed mixer. After mixing, the mixture is put into a bowl and placed in a box furnace in a pure oxygen atmosphere (inlet rate 40L / h), and the temperature is first increased to a first temperature of 520℃ at a rate of 5℃ / min and kept constant for 4h. After the constant temperature is reached, the temperature is increased to a second temperature of 762℃ at a rate of 7℃ / min and kept constant for 12.5h. After the constant temperature is reached, the temperature is lowered to room temperature at a rate of 2℃ / min, and the material B to be coated is obtained by crushing, washing, centrifuging, and drying; (2) Take 5 kg of the material B to be coated and 18 g (1500 ppm) of WTe2 and add them into a high-speed mixer for high-speed mixing and dispersion. After the mixing is completed, put them into a box furnace and heat them to the third temperature of 620°C at a rate of 3°C / min in a pure oxygen atmosphere (inlet rate of 25 L / h), and keep the temperature constant for 11 hours. After the constant temperature is completed, cool it to room temperature at a rate of 5°C / min. After the cooling is completed, the positive electrode material is obtained.
[0061] Comparative Example 4 (1) Weigh 5 kg of nickel-rich precursor Ni at a molar ratio of 1:1.03 0.92 Co 0.05 Mn 0.03 (OH)2 and 2.33kgLiOH·H2O, and 21.9g (2000ppm) Na3AlF6 are added at the same time, and mixed at a high speed in a high-speed mixer. After mixing, the mixture is put into a bowl and placed in a box furnace in a pure oxygen atmosphere (inlet rate 40L / h), and the temperature is first increased to a first temperature of 520℃ at a rate of 5℃ / min and kept constant for 4h. After the constant temperature is reached, the temperature is increased to a second temperature of 762℃ at a rate of 7℃ / min and kept constant for 12.5h. After the constant temperature is reached, the temperature is lowered to room temperature at a rate of 2℃ / min, and the material B to be coated is obtained by crushing, washing, centrifuging, and drying; (2) Take 5 kg of the material B to be coated and add it to a high-speed mixer for high-speed mixing and dispersion. After the mixing is completed, put it into a box furnace in a pure oxygen atmosphere (inlet rate 25 L / h), and heat it to a third temperature of 620°C at a rate of 3°C / min, and keep it at this temperature for 11 hours. After the constant temperature is completed, cool it to room temperature at a rate of 5°C / min. After the cooling is completed, the positive electrode material is obtained.
[0062] Comparative Example 5 (1) Weigh 5 kg of nickel-rich precursor Ni at a molar ratio of 1:1.03 0.92 Co 0.05Mn 0.03 (OH)2 and 2.33kgLiOH·H2O, and 21.9g (2000ppm) Na3AlF6 are added at the same time, and mixed at a high speed in a high-speed mixer. After mixing, the mixture is put into a bowl and placed in a box furnace in a pure oxygen atmosphere (inlet rate 40L / h), and the temperature is first increased to a first temperature of 520℃ at a rate of 5℃ / min and kept constant for 4h. After the constant temperature is reached, the temperature is increased to a second temperature of 762℃ at a rate of 7℃ / min and kept constant for 12.5h. After the constant temperature is reached, the temperature is lowered to room temperature at a rate of 2℃ / min, and the material B to be coated is obtained by crushing, washing, centrifuging, and drying; (2) Take 5 kg of the material B to be coated and 6 g (500 ppm) of WTe2 and add them into a high-speed mixer for high-speed mixing and dispersion. After the mixing is completed, put them into a box furnace and heat them to the third temperature of 620°C at a rate of 3°C / min in a pure oxygen atmosphere (inlet rate of 25 L / h). Keep the temperature constant for 11 hours, cool it to room temperature at a rate of 5°C / min, and obtain the positive electrode material after the cooling is completed.
[0063] Comparative Example 6 (1) Weigh 5 kg of nickel-rich precursor Ni at a molar ratio of 1:1.03 0.92 Co 0.05 Mn 0.03 (OH)2 and 2.33kgLiOH·H2O, and 21.9g (2000ppm) Na3AlF6 are added at the same time, and mixed at a high speed in a high-speed mixer. After mixing, the mixture is put into a bowl and placed in a box furnace in a pure oxygen atmosphere (inlet rate 40L / h), and the temperature is first increased to a first temperature of 520℃ at a rate of 5℃ / min and kept constant for 4h. After the constant temperature is reached, the temperature is increased to a second temperature of 762℃ at a rate of 7℃ / min and kept constant for 12.5h. After the constant temperature is reached, the temperature is lowered to room temperature at a rate of 2℃ / min, and the material B to be coated is obtained by crushing, washing, centrifuging, and drying; (2) Take 5 kg of the material B to be coated and 30 g (2500 ppm) of WTe2 and add them into a high-speed mixer for high-speed mixing and dispersion. After the mixing is completed, put them into a box furnace and heat them to the third temperature of 620°C at a rate of 3°C / min in a pure oxygen atmosphere (inlet rate of 25 L / h), and keep the temperature constant for 11 hours. After the constant temperature is completed, cool it to room temperature at a rate of 5°C / min. After the cooling is completed, the positive electrode material is obtained.
[0064] 2. Performance Test 2.1 Physical properties test The positive electrode materials prepared in Examples 1-8 and Comparative Examples 1-6 were subjected to scanning electron microscopy (SEM), nitrogen adsorption (specific surface area), tap density, and laser particle size tests. The test results are as follows: Figure 1-Figure 14 As shown in Table 2.
[0065] The contents of the crystal growth guiding agent and the semiconductor two-dimensional carrier auxiliary agent in Examples 1-6 are the same, but the types of the crystal growth guiding agent and the semiconductor two-dimensional carrier auxiliary agent are different. The SEM images of the positive electrode materials in Examples 1-6 are as follows: Figure 1-Figure 6 As shown by Figure 1-Figure 6 The comparison shows that Figure 1-Figure 6 The cathode materials are all spherical particles, and the surface is evenly coated with molten carrier additives. Figure 1-Figure 6 There is no obvious difference in the morphology of the positive electrode material, which means that when the addition amount of the crystal growth guiding agent and the semiconductor two-dimensional carrier additive is the same, changing the type of the crystal growth guiding agent and the semiconductor two-dimensional carrier additive has no obvious effect on the electron microscope morphology of the positive electrode material. Figure 1 and Figure 7 It can be seen that when the temperature of the first sintering increases, the primary particles on the surface of the material slightly increase. This is because the increase in sintering temperature provides a greater driving force for crystal growth, making the material more inclined to grow. Figure 1 and Figure 8 It can be seen that when the temperature of the second sintering is low, the carrier additive cannot be completely melted, and therefore cannot be evenly coated on the surface of the positive electrode material, and is generally dispersed in the form of dots on the surface of the material.
[0066] In Comparative Example 4, no carrier auxiliary agent was added. In Comparative Example 5, the amount of carrier auxiliary agent added was 500 ppm. In Comparative Example 6, the amount of carrier auxiliary agent added was 2500 ppm. The SEM images of the positive electrode materials of Comparative Examples 4-6 are shown in FIG. Figure 12-14 As shown by Figure 12-14 It can be seen from the comparison that increasing or decreasing the amount of carrier additive has a great influence on the surface morphology of material particles. Fig.12 As shown, when no carrier additive is added, the edges of the primary particles on the surface of the positive electrode material of Comparative Example 4 are clearly visible, and the surface is uneven. Fig.12 , Fig.13 , Fig.14 From the comparison, it can be seen that with the continuous increase in the amount of carrier additive added, the edges and grain boundaries of the primary particles gradually become blurred. When the amount of carrier additive added reaches 2500ppm, the surface of the material is completely covered.
[0067] 2.2 Crystal diffraction test The positive electrode materials prepared in Example 1 and Comparative Example 1 were subjected to a crystal diffraction test, and the specific steps were as follows: (1) Take a certain amount of the positive electrode materials prepared in Example 1 and Comparative Example 1, place them on the circular sample loading area of the sample table, flatten them and compact them, and ensure that the test surface of the flattened samples is smooth without obvious protrusions and depressions; (2) Scrape off the excess cathode material around the sample loading area and transfer the sample stage to the XRD diffractometer for fixation; (3) Set the scanning angle to 15-80°, the step size to 0.02°, and the scanning rate to 2° / min to perform crystal diffraction test.
[0068] The XRD diffraction patterns of the positive electrode materials of Example 1 and Comparative Example 1 are as follows: Fig.15 As shown, Table 1 lists the crystal diffraction analysis data of Example 1 and Comparative Example 1.
[0069] Table 1 Crystal diffraction analysis data table of Example 1 and Comparative Example 1
[0070] Depend on Fig.15 As can be seen from Table 1, the diffraction peaks of Example 1 and Comparative Example 1 are consistent with the diffraction peak positions of the standard card, proving that both Example 1 and Comparative Example 1 are α-NaFeO2 layered compounds. Comparative analysis data show that compared with Example 1, the crystal growth guiding agent is not added to Comparative Example 1. The unit cell parameter c / a value, grain size, and 003 / 104 peak intensity ratio of Comparative Example 1 are all reduced, while the lattice distortion increases, proving that the crystal growth guiding agent can increase the lattice parameter c, increase the interlayer spacing, and reduce the cation mixing by regulating the microstructure of the material, making the crystal structure more ordered, the diffraction peak intensity higher, and the crystallinity better.
[0071] 2.3 Electrical performance test The electrochemical performance test of the positive electrode materials prepared in Examples 1-8 and Comparative Examples 1-6 was carried out, and the specific steps were as follows: (1) Weigh the positive electrode materials, PVDF and SP prepared in Examples 1 to 8 and Comparative Examples 1 to 6 in a mass ratio of 96:2:2; (2) Add the solvent NMP into a beaker, and add the three materials weighed in step (1) while stirring, disperse and mix them evenly to form a slurry, and use a scraper to evenly coat the slurry on the surface of the aluminum foil; (3) Place the coated electrode in a vacuum drying oven at 120°C for drying, then use a slicer to punch out an electrode with a diameter of 14 mm, weigh it and set it aside for use; (4) Using lithium metal as the negative electrode, CR2025 button cells were assembled in a glove box; (5) At a temperature of 25°C, use a Xinwei battery tester to perform charge, discharge and cycle performance tests.
[0072] The electrochemical performance test and physicochemical test results of Examples 1-8 and Comparative Examples 1-6 are shown in Table 2.
[0073] Table 2 Electrochemical and physical properties test results of Examples 1-8 and Comparative Examples 1-6
[0074] As can be seen from Table 2, Examples 1-8 can have both high discharge capacity and high cycle retention rate, and their comprehensive performance is significantly better than Comparative Examples 1-6. The capacity of the battery assembled from the positive electrode materials of Examples 1-8 is above 211 mAh / g, and the cycle retention rate is above 82%. Example 7 increases the temperature of the first sintering on the basis of Example 1. After the temperature of the first sintering is increased, the primary particles of the material grow, and Li + The transmission path becomes longer and the diffusion rate decreases, so the electrical performance is slightly reduced, but the larger primary particles have better mechanical strength and crystal structure, which is conducive to the excellent cycle retention rate of the positive electrode material. Example 8 reduces the temperature of the second sintering on the basis of Example 1. The carrier additive cannot form a molten state and evenly coat the surface of the material. The point dispersion cannot effectively improve the Li + The transmission efficiency is low, and the corrosion of harmful substances produced by the decomposition of the electrolyte cannot be prevented. Therefore, compared with Example 1, the capacity utilization and cycle retention rate of the positive electrode material in Example 8 are reduced.
[0075] Comparative Examples 1 to 3 adjusted the amount of crystal growth guiding aid on the basis of Example 1. No crystal growth guiding aid was added in Comparative Example 1, and the amount of crystal growth guiding aid added in Comparative Example 2 was relatively low, while the amount of crystal growth guiding aid added in Comparative Example 2 was relatively high. It can be seen from Table 2 that when no crystal growth guiding aid was added or the amount of crystal growth guiding aid added was relatively low, the material capacity was not significantly affected. When the amount of crystal growth guiding aid added was too high, the capacity was slightly reduced (210 mAh / g), proving that adding a small amount of crystal growth guiding aid had no significant effect on the capacity of the positive electrode material. This may be because when the amount of crystal growth guiding aid added was too high, the proportion of inactive elements in the electrode material increased, resulting in a decrease in the first cycle capacity. At the same time, the crystal growth guiding agent plays an important role in the capacity retention rate of the positive electrode material. From the comparison between Comparative Examples 1-3 and Example 1, it can be seen that the cycle retention rate of the assembled battery first increases and then decreases with the increase in the amount of crystal growth guiding agent added. This may be because the crystal growth guiding agent plays a role in stabilizing the crystal structure of the material during the material synthesis process. The valence states of elements such as Na, Al, and Mg are stable, and the stress generated during the Li deintercalation process inside the lattice can slow down the damage to the structure, thereby improving the cycle stability of the material. When the amount of growth agent added is too high, too many elements such as Na, Al, and Mg occupy the active sites of the Li element, aggravating the element mixing, so the cycle retention rate decreases.
[0076] Comparative Examples 4 to 6 adjusted the amount of semiconductor two-dimensional carrier additive added on the basis of Example 1. Comparative Example 4 did not add semiconductor two-dimensional carrier additives, the amount of semiconductor two-dimensional carrier additives added in Comparative Example 5 was relatively low, and the amount of semiconductor two-dimensional carrier additives added in Comparative Example 6 was relatively high. It can be seen from Table 2 that when no semiconductor two-dimensional carrier additives are used, too little semiconductor two-dimensional carrier additives are added, or too much semiconductor two-dimensional carrier additives are added, the discharge capacity and cycle retention rate of the positive electrode material are lost to varying degrees. When no carrier additives are added, the positive electrode material is affected by processes such as water washing and centrifugation, and the residual alkali originally wrapped on the surface of the material is dissolved, exposing a lot of fresh surfaces. Under the influence of water molecule destruction, electrolyte decomposition and erosion, the surface structure of the material is severely degraded, and Li + The transmission channel is destroyed, so the discharge capacity and cycle retention rate are low, but affected by the crystal growth guiding agent, the cycle retention rate is slightly higher than that of comparative example 1; when the addition amount of semiconductor two-dimensional carrier additive is low, the coating layer formed is not enough to offset the erosion of the material surface by harmful substances produced by the decomposition of the electrolyte for a long time, and the Li transmission channel formed on the surface cannot guarantee a large amount of Li + The effective transmission of the discharge capacity and cycle retention rate are improved compared with the comparative example 4, but the overall performance is poor; when the addition amount of the semiconductor two-dimensional carrier additive is high, too much additive adheres to the surface of the positive electrode material and hinders the Li + transmission, and after a long cycle, the coated surface is destroyed to form an electrochemically inert layer, so the discharge capacity and retention rate are lower than those in Example 1.
[0077] Comparing the physical properties (specific surface area, tap density, D50) of Examples 1 to 8 and Comparative Examples 1 to 6, since the precursors used are the same, the D50 and tap density of the positive electrode materials are basically between 11.2 and 11.5 μm and 2.6 and 2.7 g / cm 3 Within the range, the addition of crystal growth guide additives and carrier additives has no significant effect on the particle size and tap size of the material. Examples 1 to 6 and Comparative Examples 1 to 3 all use the same equivalent of carrier additives to improve the interface. The carrier additives can be evenly coated on the surface of the material. The specific surface area of the positive electrode materials in Examples 1 to 6 and Comparative Examples 1 to 3 is 0.65 m 2 / g or so. Comparative Examples 4 to 6 adjusted the amount of carrier additive used. As the amount of carrier additive used increased, the specific surface area of the positive electrode material decreased accordingly. Example 7 increased the temperature of the first sintering, and the gaps between the particles of the material would decrease after the primary particles grew, so the specific surface area was slightly reduced. Example 8 reduced the temperature of the second sintering, and the carrier additive could not be well coated on the outer surface of the material, and some of it was dispersed in a point shape, so the specific surface area was increased compared with Example 1.
[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0079] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A method for preparing a positive electrode material, characterized in that: include: Mixing a nickel-rich cathode material precursor with a lithium source and a crystal growth directing agent to obtain a raw material; The raw material is subjected to a first sintering to obtain a material to be coated; The material to be coated is mixed with a semiconductor two-dimensional carrier auxiliary agent, and a second sintering is performed to obtain a positive electrode material; wherein the semiconductor two-dimensional carrier auxiliary agent includes metal telluride.
2. The method for preparing the positive electrode material according to claim 1, characterized in that: The chemical formula of the positive electrode material precursor is Ni x Co y Mn 1-x-y (OH)2, where 0.80≤x≤0.96, 0≤y≤0.10; And / or, the lithium source comprises a lithium-containing compound or a hydrate of a lithium-containing compound, and the lithium-containing compound comprises at least one of LiOH, Li2CO3, CH3COOLi, and Li2C2O4; And / or, the molar ratio of the positive electrode material precursor to the lithium source is 1:(1.02-1.06); And / or, the cationic element of the crystal growth directing aid includes at least one of Na, Al, Mg, Si, W, Zr, Sr, and Ti, and the anionic element of the crystal growth directing aid includes at least one of O, S, P, and F.
3. The method for preparing the positive electrode material according to claim 2, characterized in that: The crystal growth guiding agent includes at least one of Na3AlF6, MgSiF6, and MgAl2Si2O8; And / or, based on the mass of the positive electrode material precursor, the total mass of the cationic elements in the crystal growth directing aid is 1000-3000 ppm.
4. The method for preparing the positive electrode material according to claim 1, characterized in that: The first sintering includes: heating from room temperature to a first temperature at a heating rate of 2-10°C / min, keeping the temperature at the first temperature for 2-7 hours, heating to a second temperature at a heating rate of 5-10°C / min after the temperature is kept, keeping the temperature at the second temperature for 10-14 hours, and cooling to room temperature at a rate of 1-3°C / min after the temperature is kept constant, wherein the first temperature is 400-650°C and the second temperature is 700-800°C; And / or, the first sintering is performed in a pure oxygen atmosphere or a mixed atmosphere with an oxygen concentration of ≥90%.
5. The method for preparing the positive electrode material according to claim 1, characterized in that: The metal in the metal telluride includes at least one of W, Mo, Sn, Sb, and Bi.
6. The method for preparing the positive electrode material according to claim 5, characterized in that: The metal telluride includes at least one of WTe2, MoTe2, SnTe, and Bi2Te3; And / or, based on the mass of the material to be coated, the content of the metal element in the metal telluride is 1000-2000 ppm.
7. The method for preparing the positive electrode material according to any one of claims 1 to 6, characterized in that: The second sintering includes heating from room temperature to a third temperature at a heating rate of 2-8°C / min, keeping the temperature at the third temperature for 8-12 hours, and cooling to room temperature at a rate of 5-10°C / min after the insulation. The third temperature is 300-660°C.
8. A positive electrode material, characterized in that The positive electrode material is prepared by the preparation method according to any one of claims 1 to 7.
9. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode material according to claim 8.
10. An electrical device, characterized in that: The electrical equipment comprises the lithium-ion battery according to claim 9.
Citation Information
Patent Citations
Modified high-nickel positive electrode material coated with fast ion conductor and preparation method of modified high-nickel positive electrode material
CN108023077A
Doped and coated nickel-cobalt-aluminum ternary lithium-ion battery positive electrode material as well as preparation method and application
CN108461736A
Doped and coated nickel-cobalt-aluminum-manganese quaternary lithium-ion battery positive electrode material, preparation method and application
CN109473657A
High-nickel ternary positive electrode material and preparation method thereof
CN111244397A
Preparation method of long-circulation ternary positive electrode material
CN112194199A